An overview of influenza A virus genes, protein functions, and replication cycle highlighting important updates - Chauhan, Ravendra P.; Gordon, Michelle L. (Virus genes, 2022)
The recent research findings on influenza A virus (IAV) genome biology prompted us to present a comprehensive overview of IAV genes, protein functions, and replication cycle. The eight gene segments of the IAV genome encode 17 proteins, each having unique functions contributing to virus fitness in the host. The polymerase genes are essential determinants of IAV pathogenicity and virulence; however, other viral components also play crucial roles in the IAV replication, transmission, and adaptation. Specific adaptive mutations within polymerase (PB2, PB1, and PA) and glycoprotein—hemagglutinin (HA) and neuraminidase (NA) genes, may facilitate interspecies transmission and adaptation of IAV. The HA-NA interplay is essential for establishing the IAV infection; the low pH triggers the inactivation of HA-receptor binding, leading to significantly lower NA activities, indicating that the enzymatic function of NA is dependent on HA binding. While the HA and NA glycoproteins are required to initiate infection, M1, M2, NS1, and NEP proteins are essential for cytoplasmic trafficking of viral ribonucleoproteins (vRNPs) and the assembly of the IAV virions. The mechanisms that enable IAV to exploit the host cell resources to advance the infection are discussed. A comprehensive understanding of IAV genome biology is essential for developing antivirals to combat the IAV disease burden.